Association between chronic respiratory diseases and frailty in Chinese elderly: a population-based longitudinal study - Ting Yang; Ping He; Dawei Zhu; Dan Guo; Ruoxi Ding; Ke Huang; Yanan Zhao; Xiaolong Guan (BMJ Open Respiratory Research)
Background Chronic respiratory diseases (CRDs) have been shown to be associated with frailty, but these findings have not yet reached a consensus. The aim of this study was to investigate the association between CRDs and frailty in the elderly using a nationally representative data from China.Methods Data from the China Health and Retirement Longitudinal Study (CHARLS) were analysed, including 3309 frailty-free participants followed for three waves from 2011. Frailty was assessed using the physical frailty phenotype scale, and CRDs were conformed by self-reported physician diagnoses. Cox proportional hazard models were used to examine the association between baseline CRDs and subsequent frailty.Results Among participants (mean age 67.07 years, 51.53% male), 497 (15.02%) had CRDs. During a mean follow-up of 46 months, 273 (8.25%) participants developed frailty. The incidence rate of frailty was significantly higher in the CRDs group (37.17% per 1000 person-years vs 18.41% per 1000 person-years, p<0.01). Adjusted for covariables, participants with CRDs had a 44% higher risk of developing frailty (HR = 1.44, 95% CI: 1.08 to 1.91). Specifically, asthma only (HR=1.89, 95% CI: 1.07 to 3.33) and asthma-chronic obstructive pulmonary disease (COPD) overlap (ACO) (HR=1.79, 95% CI: 1.19 to 2.69) were associated with a higher risk of frailty among the elderly, while COPD only was not (HR=1.11, 95% CI: 0.73 to 1.65).Conclusion This study shows a significant association between CRDs, particularly asthma only and ACO, and frailty in the elderly. We need to pay attention to the frailty status of CRDs patients and consider routine screening among them in both clinical practice and community settings. Active treatment and control of CRDs are necessary to avoid frailty caused by primary lung disease progression or exacerbation.